Sistem Pendukung Keputusan Rekomendasi Penerimaan Bantuan Beasiswa Kurang Mampu Dengan Menerapkan Metode Ocra Dan Pembobotan Roc Pada Sekolah YapimMedan - Marta Zega; Muhammad Syahrizal; Ilhamsyah Ilhamsyah (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Scholarship assistance is educational assistance organized by the government, foundations or companies to help ease the burden on underprivileged students so they can continue their education and to improve the quality of human resources through education. YAPIM SMA provides scholarships to underprivileged students every year. To get the scholarship, the school sets several criteria for which students can be recommended and are entitled to receive scholarship assistance for the underprivileged. These criteria will later help the school in determining which students are entitled to get scholarships for underprivileged students. To make it easier for schools to determine students who are entitled to scholarships, it is necessary to have a decision support recommendation system that functions to help select prospective scholarship recipients who are less fortunate. In this study the authors applied the OCRA method for ranking values and the order centroid ranking method ( ROC) for the results of weighting at YAPIM schools. By implementing this decision support system, the school can easily determine students who are entitled to get underprivileged scholarships. The assessment runs objectively, accurately.